2019
DOI: 10.2754/avb201988010085
|View full text |Cite
|
Sign up to set email alerts
|

The effects of transport stress on the behaviour and adrenocortical activity of the black-and-white ruffed lemur (Varecia variegata)

Abstract: The aim of this study was to assess behavioural and glucocorticoid changes in black-and-white ruffed lemur females transported for breeding purposes between Czech ZOOs. The frequency of the presented behaviour elements was recorded via direct observation. The faecal samples were collected from the floor and subsequently the faecal glucocorticoid values were determined using specifically designed assays for faecal glucocorticoid metabolite (FGM) analysis. While the frequency of certain comfort behaviour pattern… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 44 publications
0
9
0
Order By: Relevance
“…As previous research has indicated, fGM concentrations change significantly following transfers [ 37 , 38 , 39 ], introductions [ 40 , 41 ], and veterinary procedures [ 42 ]. Sample dates were chosen to minimize the effects of these additional stressors while still providing meaningful data on transition periods.…”
Section: Methodsmentioning
confidence: 99%
“…As previous research has indicated, fGM concentrations change significantly following transfers [ 37 , 38 , 39 ], introductions [ 40 , 41 ], and veterinary procedures [ 42 ]. Sample dates were chosen to minimize the effects of these additional stressors while still providing meaningful data on transition periods.…”
Section: Methodsmentioning
confidence: 99%
“…Similarly, glucocorticoid levels in faeces during the reproduction season were analysed in red-fronted lemurs (Eulemur fulvus rufus) [17] using the analysis targeting the metabolite 11-oxo-etiocholanolone. The suitability of the analysis of the metabolite 11-oxo-etiocholanolone has also been confirmed by studies of the stress level in ring-tailed lemurs and black-and-white-ruffed lemurs by non-invasive methods [18,19].…”
Section: Introductionmentioning
confidence: 98%
“…Given their small body size and fast metabolism, changes in FGMs were expected to be measurable within one to two days after exposure to a stressor [ 1 , 10 ] as confirmed by several studies assessing changes in FGM concentrations resulting from stress, for example, in zoo-living orangutans ( Pongo spp.) [ 13 ], common marmoset ( Callithrix jacchus ), long-tailed macaque ( Macaca fascicularis ), Barbary macaque ( Macaca sylvanus ), chimpanzee ( Pan troglodytes ) and gorilla ( Gorilla gorilla ) [ 21 ], Western lowland gorilla ( Gorilla gorilla gorilla ) [ 22 ], pileated gibbons ( Hylobates pileatus ) [ 23 ], wild gray mouse lemurs [ 24 ], ring-tailed lemurs ( Lemur catta ) [ 18 ] and black-and-white ruffed lemurs ( Varecia variegata ) [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…If we look beyond zoo-based research, we find that animal handling, generally speaking, has long been considered a source of potential stress and welfare compromise in laboratory animals (Balbcombe et al, 2004;Meany et al, 1996;Meijer et al, 2007;Núñez et al, 1996). Insights into the impact of on-grounds transportation on zoo animal welfare are just beginning to accumulate (e.g., Göttert et al, 2015;Tetzlaff et al, 2016), but generally speaking, transportation is associated with physiological or behavioral stress responses (e.g., Campbell-Palmer & Rosell, 2015;Fazio et al, 2019;Tonn et al, 2016;Volfová et al, 2019). In one study focused specifically on program animals in zoos, Baird et al (2016) measured both behavioral and physiological indicators of welfare to investigate the effects of ambassador programming on three common program animals: armadillos (Lypeutes matacus, Chaetophractus vellerosus, Dasypus novemcinctus, Euphractus sexcinctus), red-tailed hawks (Buteo jamaicensis), and hedgehogs (Atelerix albiventris).…”
mentioning
confidence: 93%